Schelling against Jacobi. The possibility of a system of freedom - Guerrero Troncoso, Hernán (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The intention of this article is to show how the examination of the alleged pantheism of Spinozas’ system, which opens the Philosophical Inquiries into the Essence of Human Freedom of Schelling, presents not only his own stand concerning the Pantheism controversy, but also implies a discussion with Modern thought, particularly regarding the place, function and implications of the notion of system, and its relation to freedom. An exposition of Jacobi’s critical analysis of the history of Western Philosophy —where he asserts that the system is incompatible with the knowledge of the unconditioned— will illustrate the terms of this dialogue of the philosopher from Leonberg with the tradition.
Keywords: german Idealism; ontology; pantheism; Spinoza; will